The role of alkyl substituents in deazaadenine-based diarylethene photoswitches - Sarter, Christopher; Heimes, Michael; Jäschke, Andres (Beilstein journal of organic chemistry, 2016)
Diarylethenes are an important class of reversible photoswitches and often claimed to require two alkyl substituents at the carbon atoms between which the bond is formed or broken in the electrocyclic rearrangement. Here we probe this claim by the synthesis and characterization of four pairs of deazaadenine-based diarylethene photoswitches with either one or two methyl groups at these positions.